Globalization and Human Resource Management - Česynienė, Rima (Ekonomika, 2008)
Globalization represents the structural making of the world characterized by the free flow of technology and human resources across national boundaries as well as the spread of Information Technology and mass media presenting an everchanging and competitive business environment.The article deals with the practical consequences of globalization for human resource management (HRM). Globalization makes national culture an increasingly strategic issue that has to be faced and properly managed. The problem is the balancing of the global trends in human resource management with the influence of national culture because many aspects of HRM are affected by differences in national culture. The article analyses the major challenges arising from globalization and affecting human resource management practices in the 21st century in selected industrialized countries (United Kingdom, France, USA, Japan) and Lithuania as a new member of the EU.The general aim of the article is to analyse the problem of balancing seemingly opposing forces (globalization and the influence of national culture) and to identify trends in HRM across five countries: United Kingdom, France, USA, Japan and Lithuania.